Strategi Pembelajaran Efektif Untuk Meningkatkan Minat Baca Anak SD - Apranita, Della; Haifaturrahmah, Haifaturrahmah; Nizaar, Muhammad (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2025)
This study aims to examine various teaching strategies used by teachers to enhance reading interest among elementary school students through a Systematic Literature Review (SLR) approach. The data were obtained from relevant national and international publications published between 2015 and 2024. The review identified six main categories of effective strategies: (1) storytelling and read-aloud activities, (2) reading corners and literacy-rich classroom environments, (3) the use of digital, visual, and interactive media, (4) collaborative or group-based reading activities, (5) reward systems and positive reinforcement, and (6) parental involvement and home-based support. The findings indicate that increasing students’ reading interest cannot be achieved through a single approach, but rather through a combination of strategies tailored to learners’ needs and school contexts. This review is expected to serve as a reference for teachers, schools, and policymakers in designing literacy learning that is more creative, adaptive, and effective.